Mobile App for Child Learning with Task Reminders and Performance Statistics - Setyadinsa, Radinal; Pinastawa, I Wayan Rangga; Razaqa, Dhi'Fan; Sebayang, Axel Putra Bintang Syahkuala (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2025)
The rapid development of mobile technology has opened significant opportunities to support education, particularly in monitoring children"™s learning activities. Common challenges faced include poor time management among children, limited parental supervision, and the absence of an integrated system for task reminders and performance analysis. This research aims to develop a mobile application for Child Learning Monitoring, featuring task reminders based on notifications and performance statistics in graphical form. The study employed a Research and Development (R&D) method using the Software Development Life Cycle (SDLC) approach, which consists of requirement analysis, interface design, application implementation, testing, and evaluation. The application was developed using Android Studio with Java programming language. The task reminder feature utilizes the AlarmManager to display notifications according to the scheduled time, while performance statistics are visualized using a Pie Chart to represent the number of completed and pending tasks. Implementation results indicate that the application runs smoothly on Android devices. Functional testing using the Black Box Testing method proved that all features operate as designed. A limited user trial involving children and parents revealed that more than 80% of users found the application easy to use, beneficial, and effective in improving children"™s learning discipline. Therefore, this application serves as an innovative solution to assist children in managing their daily learning activities while providing parents with an easier way to monitor progress.